Business Strategy for Alqa Susu Toko Ibu dan Anak (ASTIA) Mother and Children Care Store - Soesilo, Trihandoyo Indroyono; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2015)
Abstract.The Micro and Small enterprises and the FMCG (Fast Moving Consumer Goods) are highly interrelated one another. The FMCG includes food and non-food everyday consumer product that are usually purchased as an outcome of small-scale consumer decision. Due to locality of the consumerâ€™s residences, some of them prefer to buy at nearby stores that offer good quality products at reasonable prices. The Alqa store is one of them. To begin the elaboration, the nature of micro small enterprises is elaborated, and then the fast moving consumer goods and its marketing will be explained afterwards. The nature of FMCG consists of the FMCG Supply Chain that reaches the consumers through marketing. Marketing deals with identifying and meeting human and social needs. In this case the Alqa Store is one of the marketing actors from the supply chain of the manufacturers before reaching the final customers. Alqa Store faces the problem of stagnant revenue, inadequate profit and intense competition with the competitors.Â